2004
DOI: 10.1117/1.1645795
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of age-related effects in human skin: A comparative study that applies confocal laser scanning microscopy and optical coherence tomography

Abstract: Skin structure and age-related changes in human skin were characterized in vivo by applying confocal laser scanning microscopy (CLSM) and optical coherence tomography (OCT). The overall effect of aging skin, derived from studies of volunteers belonging to two age groups, was found to be a significant decrease in the maximum thickness of the epidermis and flattening of the dermo-epidermal junction. At a certain depth in the dermis, well below the basal layer, a reflecting layer of fibrous structure is observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
166
3
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(190 citation statements)
references
References 41 publications
(68 reference statements)
17
166
3
4
Order By: Relevance
“…Therefore in general in OCT images, the papillary ridges are not well defined. This effect may be heightened in our study because of the demographics of our patient population; age has been shown to flatten the dermoepidermal junction [12]. While individual collagen and elastin bundles cannot be seen, their cumulative backscattering and attenuation creates a characteristic texture.…”
Section: Image Characteristicsmentioning
confidence: 92%
See 2 more Smart Citations
“…Therefore in general in OCT images, the papillary ridges are not well defined. This effect may be heightened in our study because of the demographics of our patient population; age has been shown to flatten the dermoepidermal junction [12]. While individual collagen and elastin bundles cannot be seen, their cumulative backscattering and attenuation creates a characteristic texture.…”
Section: Image Characteristicsmentioning
confidence: 92%
“…A deeper brightly reflecting layer is seen below the epidermis. By comparing OCT images with confocal microscopy images, it has been shown that this hyperintense layer in OCT images is not the epidermal-dermal junction [12]. Rather, it appears to be caused by a layer of fibrous structure in the dermis that may be due to the transition from the papillary to the reticular dermis.…”
Section: Image Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are large differences in skin thickness with respect to body site, ranging from <0.5 mm on the eyelids to more than 6 mm on the soles of the feet [24]. The decrease in epidermal thickness with ageing was found to be smaller at the temple than at the volar forearm [21,25], which may be the effect of cumulative photoageing.…”
Section: Anatomical Variationsmentioning
confidence: 99%
“…There are large differences in skin thickness with respect to body site, ranging from <0.5 mm on the eyelids to more than 6 mm on the soles of the feet [24]. The decrease in epidermal thickness with ageing was found to be smaller at the temple than at the volar forearm [21,25], which may be the effect of cumulative photoageing.The lipid composition of human stratum corneum displays striking regional variation in both content and compositional profile [23]. There is a much higher proportion of sphingolipids and cholesterol in palmoplantar stratum corneum than on extensor surfaces of the extremities, abdominal or facial stratum corneum [23].…”
mentioning
confidence: 99%